Systematic Literature Review: Peran Konseling dalam Meningkatkan Keterampilan Sosial Siswa Sekolah Menengah - Iqlima Rahma Khairunnisa; Nabila Destriyanti; Bilqis Syakira Khalda; Ruri Afriyan Hidayat; Naufaldy Nurrobi Aditya (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Social skills are an important part of student development, especially in the context of social interactions in school environments. However, the digital era and the lack of direct interactions pose unique challenges in the formation of these skills. This article aims to examine the role of counseling in enhancing students' social skills through a systematic literature review. The method used is qualitative descriptive study reviewing various recent journals and scientific publications. The results indicate that both individual and group counseling services can significantly improve students' communication abilities, empathy, cooperation, and conflict resolution. Techniques such as role playing, modeling, group discussions, and humanistic approaches have proven effective. This article recommends strengthening evidence-based counseling services in schools to support students' social skills development.